EMPLOYMENT OF MICROBES ISOLATED FROM RESIDENTIAL WASTEWATER TO DEGRADE CHLOROBENZENE - Noor Hafiza Harun; Firdausi Razali (Tropical Life Sciences Research, 2008)
The performance of microbial consortia from residential wastewater to degrade chlorobenzene (CB) was investigated. The consortia were firstly exposed to high CB concentration (i.e. 0.2 mg/l) for seven months. As a result, two most dominant survivors, denoted as 'Yellow Colony' (YC) and 'White Colony' (WC) were isolated. In a comparison study, the mixture of WC and YC yielded three times greater maximum CB specific degradation rate, Qs (7.12 x 10–6 g CB degraded/g cell per hour) than the individual WC and YC did, combined. This clarified that there was a synergistic effect of YC and WC on CB degradation. Result in a continuous culture indicated that nitrogen-enriched feed (yeast extract) has improved the critical dilution rate, Dc from 0.08 hour–1 to 0.11 hour–1. This proved that the nitrogen limitation could not be ignored. Our result also indicated that no degradation was witnessed below 0.6 ?g/l, where CB was almost undetectable by microbes below this threshold level. Outcomes of this study have provided useful parameter estimates for future up scaling works, or on site trial. Keupayaan konsortium mikrob daripada air sisa kediaman dalam penguraian klorobenzena (CB) telah dikaji. Konsortium ini terlebih dahulu didedahkan pada kepekatan CB yang tinggi (0.2 mg/l) selama tujuh bulan. Hasilnya, dua spesies yang paling dominan berjaya dipencilkan, iaitu 'Koloni Kuning' (YC), dan 'Koloni Putih' (WC). Sebagai perbandingan, gabungan YC and WC memberikan kadar penguraian spesifik CB, Qs (7.12 x 10–6 g CB terurai/g biojisim per jam) tiga kali ganda lebih tinggi berbanding hasil gabungan bagi individu WC dan YC. Ini membuktikan wujud kesan sinergistik bagi YC dan WC dalam penguraian CB. Keputusan daripada kultur selanjar menunjukkan penambahan sumber nitrogen telah meningkatkan kadar pencairan kritikal, Dc daripada 0.08 jam–1 kepada 0.11 jam–1. Ini membuktikan penghadan nitrogen dalam penguraian CB tidak boleh diabaikan. Keputusan juga menunjukkan penguraian CB tidak berlaku di bawah kepekatan 0.6 ?g/l, di mana CB tidak dapat dikesan oleh mikrob di bawah tahap ambang ini. Hasil kajian ini boleh dijadikan panduan dalam menganggar parameter-parameter untuk kerja-kerja perskalaan pada masa akan datang atau percubaan di tapak sebenar.